Effects of Drainage Volume on Changes of Blood Acidity, and Partial Arterial Pressure of Oxygen and Carbon Dioxide in Massive Pleural Efusion - Denny U. Suprapto; Adrian Tangkilisan; Wega Sukanto; Christha Tamburian; Fredrik G. Langi (Universitas Sam Ratulangi, 2022)
Abstract: Massive pleural effusion is a condition in which there is a buildup of fluid beyond normal in the pleural cavum with a volume of two-thirds of one side of the pulmonary field proven with the help of chest X-ray. Drainage of pleural effusion fluid is a management treatment for pleural effusion, but nevertheless it has complications such as pain, bleeding, pneumothorax, and pulmonary edema. Blood gas analysis is simple and essential examination in emergency medicine, which is able to provide valuable information about the acid-base status, ventilation, and oxygenation of a patient. This study aimed to analyze changes in blood acidity (pH), oxygen partial pressure (PaO2) and carbon dioxide partial pressure (PaCO2) in patients with massive pleural effusion at Prof. Dr. R. D. Kandou Hospital, Manado. This was a prospective cohort study with a longitudinal data collection design according to the cohort method. The results of the overall linear regression analysis supported the effect of drainage on PaCO2, PaO2, and pH, and indicated that the relationship between drainage volume and PaO2 was positive. Meanwhile, descriptively and statistically, there was no meaningful relationship between pH and PaCO2 and drainage volume. In conclusion, there is a positive relationship between drainage volume and PaO2, however, there is no significant relationship between pH and PaCO2 with drainage volume.Keywords: massive pleural effusion; pH; PaCO2; PaO2Â Abstrak: Efusi pleura masif adalah suatu keadaan dimana terjadi penumpukan cairan melebihi volum normal di dalam kavum pleura dengan volume duapertiga dari satu sisi lapang paru yang dapat dibuktikan dengan bantuan X foto toraks. Drainase cairan efusi pleura merupakan manajemen tatalaksana untuk efusi pleura, namun memiliki komplikasi seperti nyeri, perdarahan, pneumotorak, dan edema paru. Analisis gas darah merupakan pemeriksaan yang sederhana namun esensial dalam ilmu kedokteran gawat darurat, yang mampu memberikan informasi berharga mengenai status asam basa, ventilasi maupun oksigenasi dari pasien. Penelitian ini bertujuan untuk untuk menganalisis perubahan tingkat keasaman darah (pH), tekanan parsial oksigen (PaO2) dan karbon dioksida (PaCO2) pada pasien dengan efusi pleura massif. Jenis penelitian ialah prospektif dengan desain pengumpulan data longitudinal menurut metode kohort di RSUP Prof. Dr. R. D. Kandou Manado. Hasil analisis regresi linear secara keseluruhan menunjang efek volume drainase terhadap PaCO2, PaO2, dan pH dengan hasil hubungan volume drainase dengan PaO2 bersifat positif namun tidak didapatkan hubungan bermakna antara pH dan PaCO2 dengan volume drainage. Simpulan penelitian ini ialah terdapat hubungan positif antara volume drainase dengan PaO2, namun tidak didapatkan hubungan bermakna antara pH dan PaCO2 dan volume drainase.Kata kunci: efusi pleura massif; pH; PaCO2; PaO2